Guidelines for rhinology surgery in COVID-19 pandemic - Juvekar, Meenesh; Sarkar, Baisali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
COVID-19 disease was first identified in December 2019 in Wuhan, the capital of China's Hubei province. Amid the ongoing COVID-19 pandemic, India has witnessed a massive surge of coronavirus cases. This study reviews the measures to take by the clinicians involved in rhinology surgery in light of the recent COVID-19 pandemic. The current finding about COVID-19 infection and its relation with severe acute respiratory syndrome coronavirus 2 (SARS-CoV 2) virus is evaluated and possible safety measure guidelines to be taken while doing rhinology procedures is reviewed. The risk of coronavirus 2019 can be largely reduced by wearing personal protective equipment (PPE) kit with powered air purifying respirator, double gloves, eye protection, face shield, gown, shoe covers, limiting attendance to operation theatre, negative pressure room, using negative-pressure otolaryngology viral isolation drape (NOVID) system to cover the patient and proper removal of patient drape after operation. Additionally, low oscillation speeds of microdebrider with continuous suction is associated with low risk of aerosol transmission into the environment. Rhinology and endonasal surgeries are high risk procedures and should adhere to general guidelines set for high-risk procedures. If the proposed protocols are strictly maintained then the risk of getting infected by coronavirus is markedly reduced. In this current scenario is it mandatory to attain the emergent surgical cases with all possible precautions as mentioned and defer the rest of the cases till the pandemic gets over.